“The Fairest of Them All”: analysis of skin whitening advertisements in Malaysian English women’s magazines / Mokhtar Muhammad and Irfarina Ahmad Nazli. - Muhammad, Mokhtar; Nazli, Irfarina Ahmad (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2018)
Women have desired to attain fair skin for countless of decades, a beauty standard culturalised by the mass media. There has been a deep traditional belief that fair skin is associated with higher social status and wealth, creating a preference for fair skinned women, regardless of gender. To understand this preoccupation better, a content analysis study onto five skin whitening magazine advertisements is conducted to analyse its advertisement contents, too see if these have contributed to shaping women’s thoughts and behaviour towards attaining fair skin. These skin whitening advertisements are publish in fashion magazines circulated in Malaysia, and target women as its audience. Several themes are identified by the researcher, focusing on images and words used alongside these products to attract readers when disseminating information on the product. These findings are then recorded and interpreted to derive to the conclusion of this study, revealing that advertisements in mass media do play a significant role in shaping the perception of ‘ideal’ beauty among women, particularly through symbolic association.